Patient care pathways in acute heart failure and their impact on in-hospital mortality, a French national prospective survey. (February 2020) - Gorlicki, Judith; Boubaya, Marouane; Cottin, Yves; Angoulvant, Denis; Soulat, Louis; Guinemer, Sabine; Bloch-Queyrat, Coralie; Deltour, Sandrine; Lambert, Yves; Juillière, Yves; Adnet, Frédéric
Abstract: Background: Our purpose was to describe the care pathway of patients hospitalized for acute heart failure (AHF) and investigate whether a management involving a cardiology department had an impact on in-hospital mortality. Methods: Between June 2014 and October 2018, we included patients hospitalized for AHF in 24 French hospitals. Characteristics of the episode, patient's care pathway and outcomes were recorded on a specific assessment tool. The primary outcome was the association between patient care pathway and in-hospital mortality. The independent association between admission to a cardiology ward and in-hospital mortality was assessed through a multivariate regression model and propensity score matching. Results: A total of 3677 patients, mean age of 78, were included. The in-hospital mortality rate was 8% (n = 287) and was associated on multivariate regression with advanced age, presence of sepsis, of cardiogenic shock, high New York Heart Association (NYHA) score and increased plasma creatinine level on admission. High blood pressure and admission to a cardiology department appeared as protective factors. After propensity score matching, hospitalization in a cardiology department remained a protective factor of in-hospital mortality (OR = 0.61 [0.44–0.84], p = 0.002). Conclusion: A hospital course of care involving a cardiology department was associated with an increase in hospital survival in AHF patients. These finding may highlight the importance of collaboration between cardiologists and other in-hospitals specialties, such as emergency physicians, in order to find the best in-hospital pathway for patients with AHF. Clinical Trial NCT03903198.